(untitled) (Proceedings of the International Conference of Geological Engineering Faculty, 2022)
It is encouraged to use more than one geophysical method when conducting a field survey. It can help improve the subsurface interpretation and reduce the ambiguity inherent from inversion of geophysical method. 2D resistivity and seismic refraction methods were conducted to map and characterize the subsurface at Desasiswa Indah Kembara, Universiti Sains Malaysia, Pulau Pinang. The inversion profile shows that the subsurface has two zones with a resistivity value of 150-500 Ω m (Zone A) and 5-100 Ωm (Zone B). On the other hand, the subsurface velocity is 0.3-0.6 km/s (Zone A) and 0.75-1.5 km/s (Zone B). However, the standard reference tables of resistivity and velocity value of soil and rock show variation and overlapping values that can affect the interpretation process. Therefore, additional information is important to support geophysical interpretation. Geological method such as particle size distribution (PSD) analysis (hydrometer analysis and mechanical sieving) was conducted to assist the interpretation. Percentage of clay, silt, and sand can be obtained through the PSD graph and used for soil classification. The value of total dissolved solids (TDS) and salinity of the area are also taken on-site for the saturated area with resistivity value of 20 Ωm at a depth of 2 m. The area has TDS (138-146 mg/L), and salinity (0.007 PSU) values indicating the fresh pore-fluid characteristics. Resistivity and seismic inversion profile manage to show the underlying subsurface layers. Results from PSD analysis also has supported the interpretation of the geology of the study area where Zone A was identified as silty sand, and Zone B is identified as silt and clay.